If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -3x + -2 = 22 Reorder the terms: 4 + -2 + -3x = 22 Combine like terms: 4 + -2 = 2 2 + -3x = 22 Solving 2 + -3x = 22 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -3x = 22 + -2 Combine like terms: 2 + -2 = 0 0 + -3x = 22 + -2 -3x = 22 + -2 Combine like terms: 22 + -2 = 20 -3x = 20 Divide each side by '-3'. x = -6.666666667 Simplifying x = -6.666666667
| (-7)+(+2)= | | 6x-x+3=2+5x+1 | | y=1.6x+2 | | 2a-15=85-3a | | 2-(z+8)=6 | | -x/3+5=-2 | | x^4+2x^3+-73x^3+166x+120=0 | | 4x^2-3x+6=4x+3 | | -5-(5-5p)= | | 2x(3x-5)-7=20 | | -3k+5k+3+4k= | | 3m+10=31 | | 12x-2x+10=2(x-4) | | -26+3x=-49+14x | | c=0.5m | | -5(x+3)=-8x-3 | | 6x^2-66x+144=0 | | 9x-4(x-2)=3(x+1)-9 | | 8w-3=11 | | 10x^2-3x-55=0 | | 4x^2-5x+3=(2x-1)(-x+7) | | (8n+4)(8n^2-8n+8)=0 | | 14=x+(-2y) | | 3x-15=-50 | | 3+7x=-81 | | 7z+10-z=8z-2(2-5) | | 7c+10=70-5c | | 28-6x=13-9x | | y^2-20y+12.96=0 | | 2.5z-6.5=23.5 | | 8c+1=5c-14 | | 12x^2-68x+11= |